The Role Of PAI Teachers In Teaching Nasikh-Mansukh: Challenges And Solutions In The Post-Truth Era - Niza Putri Nurfajrin; Romlah Abubakar Askar; Munzir Suparta (Penerbit Hellow Pustaka, 2025)
The rise of the post-truth era has created new epistemological and pedagogical challenges in the teaching of Islamic Religious Education (PAI), particularly in conveying complex and nuanced concepts such as nasikh-mansukh (abrogation in Islamic law). This study aims to analyze the challenges faced by PAI teachers in teaching nasikh-mansukh in the context of a digital society marked by misinformation, emotional bias, and declining trust in authoritative religious sources. Employing a qualitative approach through library research, this study explores various scholarly perspectives, classical Islamic texts, and contemporary educational discourses. The findings reveal that many students are exposed to religious content through social media that lacks context and accuracy, leading to partial and even distorted understandings of nasikh-mansukh. Teachers often encounter difficulties in countering these misconceptions due to limited resources, inadequate training in digital literacy, and the emotional resistance of students shaped by pre-existing biases. This study proposes adaptive strategies, including contextual bridging, critical Qur’anic reading, and the integration of maqāṣid al-sharī‘ah (higher objectives of Islamic law) in teaching nasikh-mansukh. These strategies aim to reframe nasakh not as a contradiction in revelation, but as a dynamic pedagogical process that reflects divine wisdom and legal responsiveness. The research contributes to strengthening Islamic education by equipping teachers with the necessary tools to navigate religious teaching in an era dominated by post-truth dynamics.